Liquid flow spinning mass-manufactured paraffin cored yarn for thermal management and ultra-high protection. (12th April 2023) - Miao, Ying; Fu, Chiyu; Li, Luyao; Tang, Wenyang; Shang, Lulu; Chen, Dingwei; Xu, Ao; Wu, Zhanpeng; Wu, Minyong; Jia, Lili; Xu, Weilin; Su, Bin; et al.
Abstract: Thermal management and ultra-high protection textiles are critical for polar scientists, astronauts and firefighters. Phase change materials (PCMs) effectively retard huge thermal changes, and thermal damage by absorbing or releasing heat during phase transition. However, due to the materials and engineering challenges inherent in PCMs based textiles, commercial PCMs usually suffer with high rigidity, no-breath-ability, easy leakage and abrasion, limiting their potential applications. Herein, we proposed a mass-producible liquid flow spinning (LFS) method, in which molten paraffin is poured into continuous hollow silicon tubes and then wrapped by staple fibers to form paraffin-coated yarns (PCYs) on a friction spinning frame. The obtained PCYs showed enhanced mechanical properties (break strength of 7.80 N, wear resistance of 2000 cycles) due to the novel core-sheath yarn structure. Besides, thanks to the high melting enthalpy (60.967 J/g) of PCYs, the yarns showed the excellent temperature regulating effect. A double-sided joint PCYs fabric (PCYF) is fabricated to study the PCYs performance further, results show that the PCYF can withstand 10, 000 cycles of abrasion without breakage and PCMs leakage. Furthermore, owing to the much gaps provided by the stretch fibers and interweaving points, the fabric exhibits good breathability. In particular, compared with commercial PCMs based textiles, our PCYF is superior in thermal protection performance (9 °C lower). The fireproof performance is also excellent as our PCYF can withstand flame temperatures higher than 1142 °C. The PCYs production method provided here could pave the way for human thermal protection textiles. Graphical abstract: Image 1 Highlights: A liquid flow spinning strategy was proposed to fabricate the thermal management paraffin-coated yarn (PCY). The obtained PCY showed good mechanical properties and excellent thermal management ability. A double-sided joint PCYs fabric (PCYF) was fabricated, which showed high abrasion resistance, thermal management and fireproof abilities. Compared to commercial PCMs fabrics, the PCYF exhibited better thermal management performance on both human body and automobiles.